Analysis of Biological Factors Affecting the Improvement of Health Accounting from the Perspective of Monetary Disorders - GHASEMABAD, DARIUSH OMIDI; KHERADYAR, SINA; NODEH, FAZEL MOHAMMADI; CHIRANI, EBRAHIM (The journal of contemporary issues in business and government, 2021)
The present study investigates the relationship between intrinsic factors and monetary disorders for the first time in Iran. The statistical population is the banks that are members of the Tehran Stock Exchange. The sample size is based on new methods of experiments and using Sample Power software and according to the type of research relationship hypothesis which is a combination of two scale variables but abnormal, Spearman test has been used. The first hypothesis of the study based on the relationship between two variables of financial risk tolerance and monetary disorders, showed that there is a significant relationship between the variables of financial risk tolerance and monetary disorders and there is a positive and moderate relationship between variables and the first hypothesis was accepted. Moreover, based on the results, the second hypothesis has a significant relationship between the variables of financial anxiety and monetary disorders, which shows a positive and moderate relationship between the variables. The second hypothesis was accepted and finally the third test showed that there is no significant relationship between monetary outcomes variables and monetary disorders and the third hypothesis of the research was not accepted. Therefore, based on the inherent origin of the variables of financial risk tolerance and financial anxiety, it has a positive and significant relationship with monetary disorders.